Configurational Flexibility of Epimeric beta-Aminothioether-chelated Ruthenium(II) eta(6)-Arene Complex Salts - Weber, Immo; Heinemann, Frank Wilhelm; Bauer, Walter; Zenneck, Ulrich (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2009)
Five chiral beta-aminothioethers were obtained via different routes orientated oil literature protocols. Three of these beta-aminothioethers were reacted with two di-mu-chloro-bischloro[eta(6)-arene]-ruthenium(II) derivatives, resulting in the title complex salts. The complex cations exhibit three stereocenters, viz. ruthenium and sulfur atoms and the chiral benzylic carbon atom of the chelate ligand backbone. Both, ruthenium and sulfur stereocenters epimerize into a mixture of four NMR distinguishable diastereomers in equilibrium, but the designed chiral benzylic carbon atom is stable under all conditions applied so far. The relative diastereomer concentrations in solution depend mainly on the spatial requirements of the eta(6)-arene ligand rather than oil the thioether moiety. Diastereomer ratios and the absolute configurations in solution were studied by NMR and CD spectroscopy. The spectroscopic results fit to the absolute X-ray crystal structure parameters determined for the diastereomers present in the crystalline state.
Keywords: Ruthenium; Arene Complexes; beta-Aminothioether Ligands; Stereochemistry; CD Spectroscopy; Epimerization Equilibrium